Eco-Digital Trends: Consumer Behavior and Marketing Practices in the Dynamic Context of Global Warming - Fazel, Hesham (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study targets climate change awareness of 4.54 billion internet users or 56% of the world's population. It examines the reception of brand messages that bring out the aspects of ecological sustainability in the context of the cultural values of social media users.Theoretical framework: The positive link between consumer behavior and environmental responsibility was derived from a web-based survey and PLS-SEM analysis with 480 participants.Design/methodology/approach: The data obtained from the survey on 480 participants is evaluated through a web-based survey and PLS-SEM model that generates the digital platform's interlinkage of consumer behavior with climate change awareness.Findings: This research depicts a positive association between consumer behavior and buying green, challenging the established notions of green consumerism.Research, Practical & Social implications: The findings call for redesigning green consumerism in the age of digitization and underpin future research on AI-driven green marketing.Originality/ value: This study provides in-depth new insights into the role of digital consumer behavior in promoting sustainability and identifies future research directions as we approach 2030-2050.